The State’s Right to Control and Local Government Authority in the Mining Sector: A Legal-Policy Research - Adhe Ismail Ananda; La Ode Dedihasriadi; Yeni Haerani (Fakultas Hukum Universitas Lampung, 2025)
The management the mining sector is under the state’s authority as mandated by the Indonesian Constitution. The principle of Hak Menguasai Negara (State’s Right to Control) grants the state comprehensive authority over mining activities, including policy-making, licensing, and supervision. However, decentralization policies have shifted the balance of power between central and regional governments. This paper analyzes the legal and policy frameworks governing this division of authority, focusing on the role of local governments. Employing normative legal research through the examination of statutes and legal principles, the research finds that the centralization of mining permits under Law No. 3 of 2020 has significantly diminished local governments’ authority, resulting in governance inefficiencies and economic imbalances. The paper further explores asymmetric decentralization as a potential approach to harmonize state control with meaningful local government participation.